2002
DOI: 10.1053/jhep.2002.31432
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of nitric oxide in cirrhosis and portal hypertension: Too much, not enough

Abstract: C hronic liver diseases are often characterized by portal hypertension, an important component of which is increased intrahepatic vascular resistance (IHVR). We have long understood that structural changes, viewed by light microscopy, are largely irreversible with our current therapeutic tools. In supplementing liver histology with liver and vascular physiology, we have encountered the existence of dynamic, nonstructural components that are in fact, reversible.Bhatal et al. first showed in in-vitro perfused ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
343
4
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(366 citation statements)
references
References 180 publications
8
343
4
11
Order By: Relevance
“…In cirrhosis, endothelial dysfunction has been surmised by the observation of changes in levels of nitric oxide-derived by-products [61,62], flow mediated vasodilatory response of the brachial artery [63] and VWF levels [64][65][66][67][68]. Currently, there is no single marker that can detect endothelial dysfunction in patients with cirrhosis.…”
Section: Factors Tipping the Hemostatic Balance In Cirrhosismentioning
confidence: 99%
“…In cirrhosis, endothelial dysfunction has been surmised by the observation of changes in levels of nitric oxide-derived by-products [61,62], flow mediated vasodilatory response of the brachial artery [63] and VWF levels [64][65][66][67][68]. Currently, there is no single marker that can detect endothelial dysfunction in patients with cirrhosis.…”
Section: Factors Tipping the Hemostatic Balance In Cirrhosismentioning
confidence: 99%
“…9 In patients suffering from liver cirrhosis, splanchnic arterial vasodilatation occurs, due to an increased local release of nitric oxide and other vasodilators related to portal hypertension, resulting in severely impaired circulatory function. 10,11 Consequently compensatory mechanisms essential in maintenance of arterial pressure in cirrhotic patients, unfortunately result in development of marked hemodynamic disturbances known as hyperdynamic syndrome. The pregnant woman has a 20-27% chance of esophageal bleed which increases markedly in case she has demonstrable varices.…”
Section: Physiological Changes Of Pregnancymentioning
confidence: 99%
“…4,5 Increased sensitivity of the intrahepatic microcirculation to vasoconstrictors [4][5][6][7] and decreased levels of the vasodilator nitric oxide (NO) and its downstream signaling cyclic guanosine 3Ј,5Ј-monophosphate (cGMP)/protein kinase G (PKG) are responsible for this elevated contractile state. 4,8,9 We previously showed that increased RhoA/ Rho-kinase signaling essentially contributes to increased intrahepatic resistance as well as increased sensitivity to vasoconstrictors in rats with secondary biliary cirrhosis. 10 The RhoA/Rho-kinase pathway is involved in vasoconstrictor-induced contraction of vascular smooth muscle.…”
mentioning
confidence: 99%